2019
DOI: 10.1155/2019/3826495
|View full text |Cite
|
Sign up to set email alerts
|

Different Brain Connectivity between Responders and Nonresponders to Dual-Mode Noninvasive Brain Stimulation over Bilateral Primary Motor Cortices in Stroke Patients

Abstract: Noninvasive brain stimulation (NBS), such as repetitive transcranial magnetic stimulation (rTMS) or transcranial direct current stimulation (tDCS), has been used in stroke patients with motor impairment. NBS can help recovery from brain damage by modulating cortical excitability. However, the efficacy of NBS varies among individuals. To obtain insights of responsiveness to the efficacy of NBS, we investigated characteristic changes of the motor network in responders and nonresponders of NBS over the primary mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…Certainly, there are other possible explanations that require further investigation. For example, some subjects respond to tDCS, while some do not [55][56][57] and some subjects may have brain connectivity that allows the current to flow in the preferential direction [58], which may not be the case for others. Furthermore, M1 to supraorbital montages do not, in general, stimulate the motor system in a consistent way [6] and two supraorbital active electrodes may allow a great amount of current to pass through the orbit; in either of these montages, it is also possible that some structures located behind the eye (e.g., lower surface of the frontal cortex) are also affected by the stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, there are other possible explanations that require further investigation. For example, some subjects respond to tDCS, while some do not [55][56][57] and some subjects may have brain connectivity that allows the current to flow in the preferential direction [58], which may not be the case for others. Furthermore, M1 to supraorbital montages do not, in general, stimulate the motor system in a consistent way [6] and two supraorbital active electrodes may allow a great amount of current to pass through the orbit; in either of these montages, it is also possible that some structures located behind the eye (e.g., lower surface of the frontal cortex) are also affected by the stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The motor cortex is one of the most frequently reported stimulation targets for rTMS modulation in both healthy populations (Hartwigsen and Siebner, 2015;Cona et al, 2017) and those with brain disorders including movement disorders (Wagle Shukla et al, 2016;Brabenec et al, 2019), stroke rehabilitation (Ludemann-Podubecka et al, 2016;Lee et al, 2019), and other disorders (Siebner et al, 2003;Odorfer et al, 2019;Pei et al, 2019;Zhang et al, 2019). Some of these studies performed RS-fMRI before and after modulation and analyzed the network changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is large variation in the analytical methods applied from study to study. These included voxel-to-voxel based dynamic FC , graph theory using 24 ROIs (Lee et al, 2019), whole-brain graph theory (Pei et al, 2019), and seed-based FC (Brabenec et al, 2019). While it could be concluded that rTMS of the motor cortex modulates the motor network, such a conclusion appears too general since it is difficult to identify which specific brain areas are modulated.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that there is large inter-individual variability in the left motor hotspot and the premotor cortex anatomical localization using canonical methods employed in a majority of tDCS studies (e.g., TMS-defined motor hotspot 6-10,12,38-44 and PMd defined as 2.5 cm anterior to the motor hotspot 45-48 ). In particular, many individuals in the Motor Hotspot group had stimulation sites that were bordering or overlapping with the standard PMd ROIs, or somewhere between the standard M1 and PMd ROIs.…”
Section: Resultsmentioning
confidence: 93%
“…Transcranial direct current stimulation (tDCS) is a noninvasive tool that can modulate cortical excitability in human brain regions 1 . The effects of tDCS on upper limb motor control and motor rehabilitation have been widely studied (for a review see Lefebvre & Liew 2 ), and promising effects of tDCS applied over the primary motor cortex (M1), functionally localized as the motor hotspot 3 4,5 in each participant, have been demonstrated in post-stroke motor recovery 6-10 . However, a major issue that prevents tDCS from being widely adopted in clinical practice is the high inter-individual variability shown in motor behavioral or cortical physiological changes following M1 stimulation 11,12 .…”
Section: Introductionmentioning
confidence: 99%